Pengaruh Pemberian Kompres Hangat Terhadap Status Dismenore Primer Pada Mahasiswi Tingkat III Prodi DIV Bidan Pendidik STIKES Husada Borneo Tahun 2013 - Rusman Efendi; Sugeng Riyanto; Siti Ulfi; STIKES Husada Borneo; Puskesmas Gambut; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
In Indonesia, the incidence of primary dysmenorrhea occurred around 54.89%. Primary dysmenorrhea is menstrual pain that occurs since menarche and there are no abnormalities in the womb tool. The use of warm compresses on the lower abdomen during menstrual pain is expected to reduce the intensity of pain due to the widening of blood vessels resulting in increased blood circulation as well as an increase in capillary pressure. Warm compresses a method of providing a sense of warmth to the client by using the tools that lead to fluid or warm on the body requires. This study aims to determine whether there is the effect of a warm compress to the status of primary dysmenorrhea. This study used survey method using cross sectional analytic ie where variables including risk factors and variables which include the effect on the observation well at the same time. Total sampling Sampling method. The population in this study are all Level III student Prodi DIV Stikes Husada Midwife Educators in Borneo. The variables of this study is the provision of a warm compress and primary dysmenorrhea. Data analysis using chi-square test. Most respondents were female students who do warm compresses when experiencing primary dysmenorrhea which there are 59 (52.2%) respondents. Most of the respondents who do warm compresses when experiencing primary dysmenorrhea have mild dysmenorrhea status ie no 50 (44.2%) respondents. Effect of Warm Compress presence Status Of Primary Dysmenorrhea. The conclusion of this study Effect of Warm Compress Against Primary Dysmenorrhea Status. Suggestions addressed to the agency's research, science, respondents and for the community.